2015
DOI: 10.1021/acs.jproteome.5b00435
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Based Proteogenomics Reveals that Human Testis Endows Plentiful Missing Proteins

Abstract: Investigations of missing proteins (MPs) are being endorsed by many bioanalytical strategies. We proposed that proteogenomics of testis tissue was a feasible approach to identify more MPs because testis tissues have higher gene expression levels. Here we combined proteomics and transcriptomics to survey gene expression in human testis tissues from three post-mortem individuals. Proteins were extracted and separated with glycine- and tricine-SDS-PAGE. A total of 9597 protein groups were identified; of these, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 42 publications
2
71
0
Order By: Relevance
“…This observation suggests that these tissues have a significant number of uniquely expressed genes or alternative transcripts not found in other tissues. Other recent publications focusing on the analysis of Testis tissue have also found this to be true 26 .…”
Section: Resultsmentioning
confidence: 61%
“…This observation suggests that these tissues have a significant number of uniquely expressed genes or alternative transcripts not found in other tissues. Other recent publications focusing on the analysis of Testis tissue have also found this to be true 26 .…”
Section: Resultsmentioning
confidence: 61%
“…Jumeau et al 40 (PXD002367) reported finding 89 missing proteins from human spermatozoa. Zhang et al 41 (PXD002179) identified 166 missing protein groups in testis. In Supplementary Table 3, we show that only 354 of the 879 HPA testis-enriched proteins are canonical in PeptideAtlas, leaving 525 yet to be found even after these two data sets were incorporated into PeptideAtlas 2016-01.…”
Section: Concluding Remarks and New Directionsmentioning
confidence: 99%
“…P, proteins and parameters. by consultation of the Tissue Atlas at www.proteinatlas.org (visited between October 2018 and January 2019; see also LC-MS/MS study by Zhang et al [2015a]). For generating BODY1 and BODY2, we selected 2 mutually exclusive sets of protein-coding genes from the according list at www.genenames.org (Human Genome Nomenclature Committee).…”
Section: Protein Setsmentioning
confidence: 99%